EFFECTS OF DIETARY FERMENTED MEALWORM LARVAE AND STOCKING DENSITY ON MANURE AMMONIA GAS CONCENTRATIONS OF BROILERS - Serkan Yazarel; Sedat Karaman; Senay Sarica (Journal of Animal and Plant Sciences, 2025)
This study was conducted to investigate the effects of the supplementation of defatted mealworm larvae meal fermented with probiotics as a new antibacterial feed additive to the diet of broilers reared under normal- (NSD) and high- (HSD) stocking density on pH value, moisture and nitrogen content, ammonia gas concentration and urease enzyme activity of manure of broilers. A total of 450 one-day-old Ross 308 male broiler chicks were randomly distributed into 6 groups of similar mean weight, each containing 5 replicates. Experimental treatments consisted of a 2 x 3 factorial arrangement with two levels of stocking density (12 birds/m2 as NSD and 18 birds/m2 as HSD) and three different mash diets: CONT- a corn-soybean meal-based diet containing no fermented defatted mealworm larvae meal (FDM) (0%); FDMLP- the diet obtained by supplementing DM fermented with Lactobacillus plantarum to the CONT diet (0.4%); FDMLB- the diet obtained by supplementing DM fermented with Lactobacillus brevis to the CONT diet (0.4%). HSD significantly increased the pH value, moisture content, ammonia gas concentration and urease enzyme activity of manure compared as NSD, but, did not influence its nitrogen content. In addition, the FDMLP and FDMLB diets significantly decreased only the ammonia gas concentration and the urease enzyme activity of manure in broilers when compared to the CONT diet. Interaction between the stocking densities and diets significantly affected only the urease enzyme activity of manure. The results indicate that dietary supplementation of FDMLP and FDMLB as new antibacterial feed additives at the level of 0.4% can reduce ammonia gas concentration and urease enzyme activity of manure of broilers regardless of stocking density.
Keywords: ammonia gas concentration; broiler; fermented mealworm larvae; manure; stocking density; urease enzyme activity